Development and Validation of a UHPLC-MS/MS Method for Ciprofol Detection in Plasma: Application in Clinical Pharmacokinetic Studies - Zhu J; Cao Y; Zhang X; Xu B (Drug Design, Development and Therapy, 2025)
Jiaxi Zhu,1,2,* Ying Cao,2,* Xingan Zhang,2 Bo Xu2 1The First School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, 510515, People’s Republic of China; 2Department of Anesthesiology, General Hospital of Southern Theater Command of PLA, Guangzhou, Guangdong, 510010, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Xu, Department of Anesthesiology, General Hospital of Southern Theater Command of PLA, Guangzhou, Guangzhou, Guangdong, 510515, People’s Republic of China, Tel +86 13802738125, Email xubo333@hotmail.comObjective: This study aimed to develop and validate an ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method for the quantification of ciprofol in human plasma, with the goal of applying this method to pharmacokinetic studies in patients undergoing elective surgery under general anesthesia.Methods: A methanol-based protein precipitation method was employed for sample preparation, using ciprofol-d6 as the internal standard. Chromatographic separation was achieved on a Shimadzu Shim-pack GIST-HP C18 column (3 μm, 2.1× 150 mm) with a mobile phase consisting of 5 mmol·L⁻¹ ammonium acetate (A) and methanol (B). The flow rate was maintained at 0.4 mL·min⁻¹, and the column temperature was set at 40°C. Detection was performed using electrospray ionization (ESI) in negative ion mode with multiple reaction monitoring (MRM). The quantification ion pairs were m/z 203.100→ 175.000 for ciprofol and m/z 209.100→ 181.100 for the internal standard.Results: Ciprofol exhibited excellent linearity across the concentration range of 5 to 5000 ng·mL⁻¹ (r > 0.999). The intra-batch and inter-batch precision values were within 4.30% to 8.28%, and the relative deviation ranged from − 2.15% to 6.03%. The extraction recovery rate was 87.24% to 97.77%, and the matrix effect relative standard deviation (RSD) was less than 15%.Conclusion: The developed UHPLC-MS/MS method is simple, rapid, accurate, and highly specific, making it suitable for the determination of ciprofol plasma concentrations and pharmacokinetic studies in clinical settings. This method provides a reliable analytical tool for future research on ciprofol in complex biological matrices.Keywords: ciprofol, UHPLC-MS/MS, pharmacokinetics